Translating evidence into policy in low-income countries: lessons from co-trimoxazole preventive therapy - Eleanor Hutchinson; Benson Droti; Diana Gibb; Nathaniel Chishinga; Susan Hoskins; Sam Phiri; Justin Parkhurst (Bulletin of the World Health Organization)
In the April 2010 issue of this journal, Date et al. expressed concern over the slow scale-up in low-income settings of two therapies for the prevention of opportunistic infections in people living with the human immunodeficiency virus: co-trimoxazole prophylaxis and isoniazid preventive therapy. This short paper discusses the important ways in which policy analysis can be of use in understanding and explaining how and why certain evidence makes its way into policy and practice and what local factors influence this process. Key lessons about policy development are drawn from the research evidence on co-trimoxazole prophylaxis, as such lessons may prove helpful to those who seek to influence the development of national policy on isoniazid preventive therapy and other treatments. Researchers are encouraged to disseminate their findings in a manner that is clear, but they must also pay attention to how structural, institutional and political factors shape policy development and implementation. Doing so will help them to understand and address the concerns raised by Date et al. and other experts. Mainstreaming policy analysis approaches that explain how local factors shape the uptake of research evidence can provide an additional tool for researchers who feel frustrated because their research findings have not made their way into policy and practice.